Sequential gene expression analysis of myelodysplastic syndrome transformation identifies HOXB3 and HOXB7 as the novel targets for mesenchymal cells in disease - Chunlai Yin; Yanqi Li; Cheng Zhang; Shizhu Zang; Zilong Wang; Xue Yan; Tonghui Ma; Xia Li; Weiping Li (BMC Cancer, 2024)
Abstract Background Myelodysplastic syndrome (MDS) is known to arise through the pathogenic bone marrow mesenchymal stem cells (MSC) by interacting with hematopoietic stem cells (HSC). However, due to the strong heterogeneity of MDS patients, it is difficult to find common targets in studies with limited sample sizes. This study aimed to describe sequential molecular changes and identify biomarkers in MSC of MDS transformation. Methods Multidimensional data from three publicly available microarray and TCGA datasets were analyzed. MDS-MSC was further isolated and cultured in vitro to determine the potential diagnostic and prognostic value of the identified biomarkers. Results We demonstrated that normal MSCs presented greater molecular homogeneity than MDS-MSC. Biological process (embryonic skeletal system morphogenesis and angiogenesis) and pathways (p53 and MAPK) were enriched according to the differential gene expression. Furthermore, we identified HOXB3 and HOXB7 as potential causative genes gradually upregulated during the normal-MDS-AML transition. Blocking the HOXB3 and HOXB7 in MSCs could enhance the cell proliferation and differentiation, inhibit cell apoptosis and restore the function that supports hematopoietic differentiation in HSCs. Conclusion Our comprehensive study of gene expression profiling has identified dysregulated genes and biological processes in MSCs during MDS. HOXB3 and HOXB7 are proposed as novel surrogate targets for therapeutic and diagnostic applications in MDS.